THE INFLUENCE OF USER EXPERIENCE, INFORMATION SYSTEM, AND CONSUMER PRODUCT ON CONSUMER LOYALTY OF FRUIT AND VEGETABLE MOBILE APPLICATION - Karunia, Karunia; Setiawan, Budi; Riana, Fitria Dina (Agricultural Socio-Economics Journal, 2023)
There are various obstacles in the development of fruit and vegetable mobile applications such as bad user experience, unresponsive service, inaccurate information, and products or prices that do not meet consumer expectations. This study analyzes the effect of user experience, information systems, and consumer products consumer loyalty through of fruit and vegetable online shopping mobile applications. This study uses a survey method by collecting data from 100 respondents selected by accidental sampling. The data in this study is analyzed using descriptive analysis and SEM-PLS. The results show that each variable, including user experience, information systems, and consumer products, positively and significantly affects the satisfaction variable. Furthermore, the direct effect of information systems, consumer products, and satisfaction variables on consumer loyalty is also positive and significant. However, the user experience variable has an insignificant effect on loyalty. The most influential variable was satisfaction. Therefore, customer satisfaction must be maintained and improved to achieve higher loyalty. Furthermore, the indirect effect of each variable which includes user experience, information systems, and consumer products, has a positive and significant effect on the loyalty variable through satisfaction as mediating variable. The most significant variable is consumer product.  However, the average value of this variable is the lowest compared to the other variables. Therefore, companies need to focus more on maintaining and improving it. This research provides valuable insights for companies in developing mobile applications that can improve user experience, provide relevant information through information systems, and produce quality of consumer products to increase consumer satisfaction and loyalty in purchasing fruit and vegetables.